Challenges facing e- learning during COVID- 19 Pandemic from teachers' perceptions - Awwad, Ahmad Reyad Ahmad; Hoorani, Ashwaq Imad Rawhi (Journal of Educational and Psychological Sciences, 2022)
The study aimed to investigate the challenges that facing the e- learning during COVID- 19 pandemic as teachers perceived. To achieve the study goals, we followed the quantitative approach, and we applied the descriptive and deductive analysis. Data collecting tool was a questionnaire. A sample of (390) teachers was randomly selected from among the study population of (37,573) teachers working in the Palestinian Ministry of Education- West Bank according to the Palestinian Central Bureau of Statistics (2020). The results revealed that the means of the barriers as a whole was mean (3.26). The barrier of the student level was the highest barrier of the e- learning mean (3.64), The school level barrier was mean (3.33). The curriculum level barrier was mean (3.10). The lowest barrier was the teacher level barrier mean (3.00). There was a vigorous positive relationship between the barrier of the student level and the barrier of the school level and curriculum level barrier, and there were no differences in disabilities related to the teachers' demographic background. The study recommended training students to utilize the e- learning, and providing teachers with necessary knowledge and skills of e- learning.
Keywords: Challenges; e- learning; teachers' perceptions; pandemic; COVID- 19